2019
DOI: 10.1371/journal.pone.0214847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of p53 status on TRAIL-mediated apoptotic and non-apoptotic signaling in cancer cells

Abstract: Due to their ability to preferentially induce cell death in tumor cells, while sparing healthy cells, TNF-related apoptosis-inducing ligand (TRAIL) and agonistic anti-TRAIL-R1 or anti-TRAIL-R2-specific antibodies are under clinical investigations for cancer-treatment. However, TRAIL-Rs may also induce signaling pathways, which result in malignant progression. TRAIL receptors are transcriptionally upregulated via wild-type p53 following radio- or chemotherapy. Nevertheless, the impact of p53 status on the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…This protein activates the extrinsic pathway by inducing FAS and promoting apoptosis through an element located in intron 1, which binds to FAS promoter regions and reaches maximum transactivation [106]. Its mechanisms through DNA damage may also be implicated in DR5 activation and consequent activation of CASP8 and Poly ADP-ribose polymerase (PARP), with this relationship being a potential therapeutic target in cancer treatment [107]. Recently, a component named Ziyuglycoside I (Ziyu I) was reported to be capable of inducing mitochondrial dependent apoptosis in human WERI-Rb-1 Retinoblastoma cells due to increased expression of p53 [108].…”
Section: Intrinsic and Extrinsic Pathwaysmentioning
confidence: 99%
“…This protein activates the extrinsic pathway by inducing FAS and promoting apoptosis through an element located in intron 1, which binds to FAS promoter regions and reaches maximum transactivation [106]. Its mechanisms through DNA damage may also be implicated in DR5 activation and consequent activation of CASP8 and Poly ADP-ribose polymerase (PARP), with this relationship being a potential therapeutic target in cancer treatment [107]. Recently, a component named Ziyuglycoside I (Ziyu I) was reported to be capable of inducing mitochondrial dependent apoptosis in human WERI-Rb-1 Retinoblastoma cells due to increased expression of p53 [108].…”
Section: Intrinsic and Extrinsic Pathwaysmentioning
confidence: 99%
“…Thus, the downregulation of Bcl-2 protein may also be a reason for the increased p53 expression. Additionally, p53 negatively regulates Muc2 and participates in the TRAIL mediated apoptotic pathway [9][10][11][12][13][14][15], so the upregulation of TRAIL by Amuc_1434* may be a reason for its degradation of Muc2. In addition, studies have shown that there is negative regulation between Bcl-2 protein and intracellular ROS [32].…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of p53, which is a tumor-suppressor gene, is responsible for 70% of CRC cases, so failure of apoptosis is a major factor in the transition from adenoma to CRC [12,13]. p53 also participates in the tumor-necrosis-factor-related apoptosis-inducing ligand (TRAIL)-mediated apoptotic pathway, which plays a role in the apoptotic process of colorectal cancer cells [14,15]. As a result, activation of the apoptosis of colon cells is of vital importance for controlling the progression of CRC [16].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the tumor suppressor p53, is well known to positively modulate TRAIL expression by binding to the promoter region of TRAIL at 346 and 625 bp upstream of the transcription start site, suggesting that it triggers TRAIL-mediated cancer cell death [21]. Recently, Willms et al, also reported that because p53 can activate apoptotic proteins such as Bax and Bid, it is an important inducer of DR-mediated apoptosis in cancer cells [22]. This study revealed that I3M enhanced apoptosis in HCT116 p53 +/+ cells by activating DR5 and TRAIL expression.…”
Section: Discussionmentioning
confidence: 99%